Microbial food web dynamics in the oceanic Gulf of Mexico. (15th April 2021) - Landry, Michael R; Selph, Karen E; Stukel, Michael R; Swalethorp, Rasmus; Kelly, Thomas B; Beatty, Jennifer L; Quackenbush, Cameron R
Abstract: Phytoplankton growth and microzooplankton grazing rates were measured in repeated profiles of dilution experiments incubated in situ on a drift array in order to assess microbial production and food web characteristics in the oligotrophic bluefin tuna spawning habitat of the Gulf of Mexico (May peak spawning seasons, 2017–2018). Grazing often exceeded growth with the processes more balanced overall in the surface mixed layer, but biomass accumulated in the mid-euphotic zone. Community production estimates (260–500 mg C m −2 day −1 ) were low compared to similar open-ocean studies in the Pacific Ocean. Prochlorococcus was a consistent major contributor (113–204 mg C m −2 day −1 ) to productivity, while diatoms and dinoflagellates (2–10 and 4–13 mg C m −2 day −1, respectively) were consistently low. Prymnesiophytes, the most dynamic component (34–134 mg C m −2 day −1 ), co-dominated in 2017 experiments. Unexpected imbalances in grazing relative to production were observed for all picoplankton populations ( Prochlorococcus, Synechococcus and heterotrophic bacteria), suggesting a trophic cascade in the absence of mesozooplankton predation on large microzooplankton. Study sites with abundant larval tuna had the shallowest deep chlorophyll maxima and significant net positive phytoplankton growth below the mixed layer.